Conspiratorial Reasoning and Economics - Madalina Calance; Paula-Elena Diacon; Andreea-Nicoleta Donici (CES Working Papers, 2014)
The unintelligibility of the social and economic phenomena is due to isolation from the various backgrounds that has driven and maintained them. The conspiratorial reasoning insists over those backgrounds and focuses on identifying the intentionality in the primary cause. Throughout history, global economic relations have been ordered by private goals, which often subordinated to the desire for wealth or power; the market and the natural order had been oppressed by the state interventionism and by the will of some political powerful groups. In this context, we believe that the conspiratorial reasoning can be an instrument of the economic analysis, by pointing the specific political and economic interests that rule over the apparent hazard of interests. This paper aims to illustrate the peculiarities of the conspiratorial reasoning, as an alternative, beneficial reasoning, which can guide us to the answers we need in a world of paradoxes and coincidences.
Keywords: B49; Z13; 330; Conspiracy theory; Conspiratorial reasoning; Economics